As segmentações não-convencionais da escrita inicial: uma discussão sobre o ritmo linguístico do português brasileiro e europeu - Cunha, Ana Paula Nobre da (2010)
This dissertation, which is based on the analysis of non-conventional segmentation data produzed by Brazilian and Portuguese children, shows the importance of initial writing data in order to discuss the linguistic rhythms of Brazilian Portuguese (BP) and European Portuguese (EP). The data were collected in texts which had been spontaneously written by Brazilian and Portuguese children who were attending the first grades in Elementary School (Pelotas, RS, Brazil) and the Basic School (Porto, Portugal). All texts belong to the a database named Banco de Textos de Aquisição da Escrita, at the Universidade Federal de Pelotas (FaE UFPel). Studies of rhythm in Phonology have been rather polemical and controversial, mainly the ones that discuss the rhythmic classification of languages. Abaurre and Galves (1998), based on an optimalist and minimalist approach, have developed a study of the rhythmic differences between BP and EP. The authors believe that the rhythm of every language is the result of the hierarchization of three principles: the integrity of the phonological word , the trochaic foot , and the foot binarity . After the detailed data description and analysis which link the prosodic constituents, the phonological processes and the stress, the central issue of this study was determined in the light of Abaurre and Galves s proposal (1998). Nonconventional segmentation such as tever ( para te ver melhor to see you better ), in BP, and parate ( para te ver melhor to see you better ), in EP, show that the directionality that the clitic uses to associate to the content word proclitic in BP and enclitic in EP may be evidence of the rhythm in writing (according to CARVALHO, 1989). Regarding the formation of rhythmic groups, the data of this study agree with Abaurre and Galves s (1998) and also show different hierarchization of principles in BP and EP. The integrity of the phonological word is found in the highest level in the Brazilian variety, whereas the trochaic foot has supremacy over the other principles in EP. Therefore, it can be concluded that the data analyzed in this study, collected from written texts, show evidence of rhythmic differences in both Portuguese varieties